Reduced OFF-axis haze in polymer-dispersed liquid crystals. Issue 9 (15th July 2017) - De Filpo, Giovanni; Mashin, Alexander I.; Beneduci, Amerigo; Chidichimo, Giuseppe
ABSTRACT: Polymer-dispersed liquid crystals (PDLCs) are composite materials formed by micron-sized droplets of liquid crystals (LCs) dispersed in a polymer matrix, which can be turned from an opaque state to a transparent one by application of a suitable electric field. PDLCs have been proposed in applications related to the control of light transmittance on large surfaces (light shutters, displays, rear mirrors). Despite several advantages, PDLCs' main drawback is haze, i.e. the fast decay of transmission at large viewing angles. In this paper, a method for achieving highly transparent PDLC devices over a wide range of viewing angles is proposed. The method is based on the use of PDLCs with tilted elongated LC droplets and driven by opportune electric fields, which are experimentally calculated and able to ensure an almost constant value for OFF-axis transmittance. Graphical Abstract: